2008
DOI: 10.1371/journal.pone.0002978
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Dried Somatic Cells Direct Embryonic Development after Nuclear Transfer

Abstract: The natural capacity of simple organisms to survive in a dehydrated state has long been exploited by man, with lyophylization the method of choice for the long term storage of bacterial and yeast cells. More recently, attempts have been made to apply this procedure to the long term storage of blood cells. However, despite significant progress, practical application in a clinical setting is still some way off. Conversely, to date there are no reports of attempts to lyophilize nucleated somatic cells for possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 31 publications
2
74
0
Order By: Relevance
“…This indicates that the freezedrying process is the more likely cause of the low success rate. However, Loi et al reported that blastocysts could be produced from freeze-dried sheep somatic cells with a success rate equivalent to that for fresh cells [8]. Even after storage for 3 years at room temperature, freeze-dried somatic cells still had the developmental potential for blastocyst formation following nuclear transfer.…”
Section: Nuclear Transfer Using Freeze-dried Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the freezedrying process is the more likely cause of the low success rate. However, Loi et al reported that blastocysts could be produced from freeze-dried sheep somatic cells with a success rate equivalent to that for fresh cells [8]. Even after storage for 3 years at room temperature, freeze-dried somatic cells still had the developmental potential for blastocyst formation following nuclear transfer.…”
Section: Nuclear Transfer Using Freeze-dried Cellmentioning
confidence: 99%
“…We have already succeeded in producing live cloned mice from mouse somatic cells frozen for 16 years [7], and this suggests that the viability of donor cells is not important for producing the next generation using nuclear transfer. Recently, Loi et al reported that sheep blastocysts could be generated from freeze-dried somatic cells with a similar success rate as for fresh cells following storage at room temperature for 3 years [8]. This was the first attempt to use freeze-dried somatic cells for nuclear transfer, but that study only demonstrated the developmental potential to the blastocyst stage rather than the preservation of nuclear function.…”
mentioning
confidence: 99%
“…To date, embryonic development after ICSI with freeze-dried sperm heads has been reported in humans (Katayose et al, 1992;Kusakabe et al, 2008), hamster (Katayose et al, 1992), cattle (Keskintepe et al, 2002;Martins et al, 2007), pigs (Kwon et al, 2004), rhesus macaque (Sanchez-Partida et al, 2008), cats (Moisan et al, 2005;Ringleb et al, 2011) and fish (Poleo et al, 2005), and live offspring were reported in mice (Wakayama & Yanagimachi, 1998;Kaneko et al, 2003;Ward et al, 2003), rabbits (Yushchenko, 1957;Liu et al, 2004), rat Hochi et al, 2008), fish (Poleo et al, 2005) and horses (Choi et al, 2011). Storage at room temperature would be ideal, and at least for mid-range duration it appear to be fine (3 years storage of somatic cells; Loi et al, 2008a). High-temperature storage, however, might be damaging to DNA integrity according to some (Kaneko & Nakagata, 2005;Hochi et al, 2008) but not all Klooster et al, 2011) researchers.…”
Section: Sperm Dryingmentioning
confidence: 99%
“…Somatic cells from a wide variety of sources can be used for this purpose. Such diverse sources include cells from tissues preserved without cryoprotectant at -80ºC for more than a decade, or cells from tissues kept at -20ºC for as long as 16 years (Hoshino et al, 2009), cells isolated from mummified animals (Kato et al, 2009), freeze-dried somatic cells (Loi et al, 2008a;Ono et al, 2008; see next section), semen-derived somatic cells (Nel-Themaat et al, 2008a;Nel-Themaat et al, 2008b;Liu et al, 2010), cells collected postmortem (Oh et al, 2008), cell line (Campbell et al, 1996), and of course both fetal and adult cells are suitable for this purpose (Wilmut et al, 1997). SCNT has indeed an obvious potential for the multiplication of rare genotypes (Corley- Smith & Brandhorst, 1999;Loi et al, 2008a;Loi et al, 2008b), but its wide application is prevented by the currently low efficiency in terms of offspring outcome.…”
Section: Somatic Cells Cryopreservation For Scntmentioning
confidence: 99%
“…However, although all donor cells were dead after thawing, the donor cells were frozen in a medium including polyvinylpyrrolidone, which is known to exhibit cryoprotectant effect (6). Freeze-dried cells were also used for these nuclear transfer attempt, and all cells were dead after rehydration (7,8). Although cloned embryos were obtained from those dead cells following nuclear transfer, no cloned offspring were obtained.…”
mentioning
confidence: 99%